Analysis of the Implementation of Social Emotional Learning to Address Bullying Behavior in Elementary Schools - Kristianto, Andika; Wakhudin, Wakhudin (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the implementation of social-emotional learning and its contribution to social-emotional dynamics in overcoming bullying behavior among elementary school students. The research used a qualitative method with a case study approach, where data was collected through participatory observation, in-depth interviews, and documentation. The subjects were three sixth-grade teachers at elementary schools. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing/verification. The results showed that SEL had been implemented through various strategies, such as emotion regulation techniques (STOP), reflection journals, role-playing, group discussions, and collaborative learning in line with the CASEL framework. However, the implementation varied greatly and depended on the individual initiative of teachers without the support of structured school policies. The characteristics of the implementation reveal fundamental weaknesses in the form of dependence on external teacher control, a reactive and short-term orientation, and the absence of a systematic evaluation mechanism, resulting in students' social and emotional skills not yet being internalized independently. SEL has an important contribution to bullying prevention through strengthening emotional regulation, developing empathy, and forming social awareness, but its effectiveness is not automatic and is highly determined by the quality of pedagogical implementation and structural support from the school. This study confirms that the potential of SEL as a preventive approach to bullying behavior can only be optimally realized if it is implemented systematically, consistently, and sustainably with comprehensive school policy support, adequate teacher professional development, and active collaboration with all education stakeholders.